2021
DOI: 10.1108/jsocm-10-2020-0214
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing and higher education: partnering to achieve sustainable development goals

Abstract: Purpose Accomplishing the United Nations’ Sustainable Development Goals (SDGs) is imperative for societies to meet their grand challenges. Achieving these goals by 2030 requires sustainability change agents with a can-do-attitude. This study aims to show how institutions of higher education can become partners for social marketing in bringing forward such change agents. Design/methodology/approach Taking a case study approach, this paper examines a master’s programme to identify factors relevant to educating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…During this time, social marketing scholarship and practice have investigated various types of sustainable behaviour, including recycling (Anghelcev and Sar, 2014), reducing food waste (Hodgkins et al , 2019) and efficient household energy use (Butler et al , 2016). Indeed, there has been renewed interest and recognition of the important role social marketing can play in sustainability, particularly in achieving the United Nations’ Sustainable Development Goals for 2030 (Hübscher et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During this time, social marketing scholarship and practice have investigated various types of sustainable behaviour, including recycling (Anghelcev and Sar, 2014), reducing food waste (Hodgkins et al , 2019) and efficient household energy use (Butler et al , 2016). Indeed, there has been renewed interest and recognition of the important role social marketing can play in sustainability, particularly in achieving the United Nations’ Sustainable Development Goals for 2030 (Hübscher et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, recently, social marketing studies have shown how institutions of higher education can become partners in social marketing efforts, creating a motivating learning environment for students as potential sustainability change agents (Hübscher et al , 2021). Films and documentaries are effective media for educating people and increasing their consciousness.…”
Section: Social Marketing Implications For Aligning Consumers’ Restle...mentioning
confidence: 99%
“…Sustainability is also an integral part of universities which attracts significant attention worldwide due to pressure from society, students and policy (Radwan and Khalil, 2021). Some universities in Malaysia and Indonesia have become sustainable universities as sustainability is an essential agent in changing students’ sustainable awareness and behaviour (Hübscher et al, 2021). Sustainability knowledge and new educational practices related to sustainability are essential (Sclater, 2018).…”
Section: Introductionmentioning
confidence: 99%